Neolithization and Population Replacement in Britain: An Alternative View. Issue 3 (August 2022) - Thomas, Julian
Abstract : Investigation of British Mesolithic and Neolithic genomes suggests discontinuity between the two and has been interpreted as indicating a significant migration of continental farmers, displacing the indigenous population. These incomers had already acquired some hunter-gatherer genetic heritage before their arrival, and this increased little in Britain. However, the proportion of hunter-gatherer genetic ancestry in British Neolithic genomes is generally greater than for most contemporary examples on the continent, particularly in emerging evidence from northern France, while the ultimate origin of British Neolithic populations in Iberia is open to question. Both the date calculated for the arrival of new people in Britain and their westerly origin are at odds with other aspects of the existing evidence. Here, a two-phase model of Neolithization is proposed. The first appearance of Neolithic things and practices significantly predated a more substantial transfer of population, creating the conditions under which new communities could be brought into being. The rather later establishment of a major migration stream coincided with an acceleration in the spread of Neolithic artefacts and activities, as well as an enrichment of the Neolithic material assemblage.